Comparative Analysis of the Rights of Students with Disabilities on the Examples of Georgia and Some European Countries - Khatiashvili, Khatia; Chanturia, Gvanca ("Intercultural Dialogues" Transactions, 2023)
In this article we discuss the rights of students with disabilities in Georgia and European countries, legislative changes and international political documents. Today the rights of persons with disabilities are one of the areas on which attention is focused in almost all developed countries and the protection of their rights is one of the important, priority and noteworthy issues. All modern researchers rely on international norms and recognize their influence in the issues of education of people with disabilities. All political documents talk about the equal rights of disabled people and their protection. The disadvantages of inclusive education in higher education institutions are caused by the absence of such problems as, first of all, the difficulty of developing educational programs adapted for students with disabilities, on the other hand, with the insufficient material and technical base and also with a low level of training of professors and teachers. There are many problems that appear in terms of implementation of inclusive education in higher education institutions, but there are also recommendations for their elimination.